Peranan Media Sosial dan Harga Terhadap Keputusan Pembelian Jasa Rekaman di Demores Rumah Musik - Bimantara, I Made Wira (Jurnal Pendidikan Ekonomi Undiksha, 2021)
This study aimed to examine (1) the simultaneous social media and price on purchasing decisions, (2) the partial effect of social media on purchasing decisions, and (3) the partial effect of price on recording service at Demores Rumah Musik. The research design used was a casual quantitative reseach design.Data was collected using an instrument in the form of a questionnaire that had a total of 13 statements, then the data obtained were analyzed using multiple linear regression analysis. The results of this study indicate that (1) social media and price have a significant effect on purchasing decisions, (2) social media has a positive and significant effect on purchasing decisions, and (3) price has a positive and significant effect on Demores Rumah Musik purchasing decisions.